2021
DOI: 10.3390/w13172385
|View full text |Cite
|
Sign up to set email alerts
|

Two Mechanisms of Earthquake-Induced Hydrochemical Variations in an Observation Well

Abstract: Due to frequent large earthquakes in the Lanping-Simao fault basin—located in China’s Yunnan Province—the Simao observation well has observed groundwater discharge, as well as Ca2+, Mg2+, and HCO3− concentrations every day between 2001–2018. Over 18 years of observations, M ≥ 5.6 earthquakes within a radius of 380 km from the well were seen to cause hydrochemical variations. In this study, we investigated CO2 release and groundwater mixing as possible causes of regional earthquake precursors, which were caused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Underground water geochemistry has played an important role in inferring geotectonic activity. Hydrological effects occurring during strong earthquake cycles have been observed both recently and historically (Scholz et al, 1973;King, 1986;Linde et al, 1988;Thomas, 1988;Kitagawa et al, 1996;Wang et al, 2001;Jonsson et al, 2003;Yang et al, 2011;Li et al, 2014;Skelton, 2014;Yan et al, 2014;Yuce et al, 2014;Manga and Wang, 2015;Rosen et al, 2018;Martinelli and Tamburello, 2020;Nakagawa et al, 2020;Fu et al, 2021;Zhang et al, 2021;Zhou et al, 2021). Large, localized, and sustained fluid pressures could account for weakness of deep-seated fault (Fulton and Saffer, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Underground water geochemistry has played an important role in inferring geotectonic activity. Hydrological effects occurring during strong earthquake cycles have been observed both recently and historically (Scholz et al, 1973;King, 1986;Linde et al, 1988;Thomas, 1988;Kitagawa et al, 1996;Wang et al, 2001;Jonsson et al, 2003;Yang et al, 2011;Li et al, 2014;Skelton, 2014;Yan et al, 2014;Yuce et al, 2014;Manga and Wang, 2015;Rosen et al, 2018;Martinelli and Tamburello, 2020;Nakagawa et al, 2020;Fu et al, 2021;Zhang et al, 2021;Zhou et al, 2021). Large, localized, and sustained fluid pressures could account for weakness of deep-seated fault (Fulton and Saffer, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The composition of groundwater affected by tectonic activity in fault zones or by earthquakes will be exceptional, and the injection of CO 2 is proposed as a main mechanism for the generation of the abnormalities [1][2][3][4][5][6].…”
Section: Relationship Between Water Chemistry Anomaly Of the Boiling-...mentioning
confidence: 99%
“…Seismic activities along faults or fractures may disturb the original equilibrium state of the water-rock interaction in the crust, resulting in abnormal changes in the chemical composition of gas and water in the groundwater [1][2][3][4][5][6]. Long-term observations have shown that the composition of groundwater near the Earth's surface and the gas composition in the soil sensitively record the stress and strain state of the Earth's crust [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…A variety of geophysical and geochemical observations, ranging from ground-related deformation patterns (GPS, SAR, etc.) (Bürgmann et al, 2000;Zhao et al, 2020) to pre-earthquake changes (geochemical, electromagnetic, hydro-geological, geodetic, or thermodynamic) (Huang F. Q. et al, 2017;Zhou et al, 2020;Chen et al, 2021;Martinelli et al, 2021;Zhou et al, 2021), recorded by ground-based (Li et al, 2022) or satellite-based techniques (Li et al, 2020) may be related to stress variations in the lithosphere (Luo et al, 2023) prior to an eventual large earthquake (Zhao et al, 2022). Even though much effort has been invested, the earthquake "elephant in the room" is still in the process of being understood.…”
mentioning
confidence: 99%